Study on The effect of magnetic and electrical fields on fetal sexing - Ghalehsefid, Seyed Sajjad Salehi (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
Magnetic and electrical fields in addition to causing mental and physical illness can also affect fertility and fetal sex. The study on over 106 employees working in distribution, transmission and generation of electricity in the Khuzestan (South West Iran) province showed that employees who are at risk of permanent fields have fewer male children while Based on these studies, the employees who live away from the electrical equipment have more boys. The results of this study can strengthen the hypothesis of electric and magnetic fields effects on fetus sex.